Efficacy and safety evaluation of dexmedetomidine for postoperative patient controlled intravenous analgesia: A systematic review and meta-analysis - Chen, Rui; Sun, Shujun; Li, Yufan; Dou, Xiaoke; Dai, Maosha; Wu, Yan; Lin, Yun (Frontiers in Pharmacology, 2022)
Objective: To investigate the efficacy and safety of dexmedetomidine (DEX) for postoperative patient controlled intravenous analgesia (PCIA). Measurements: Two investigators independently searched Pubmed, Embase, Scopus, Cochrane Library and CBM for randomized controlled trials of DEX for PCIA. Main Results: Thirty-seven studies with a total of 5409 patients were included in this meta-analysis. Compared with analgesics alone, DEX for PCIA reduced pain score at 24 h (mean difference [MD] = -0.70; 95% confidence interval [CI]: -0.85, -0.54; P < 0.00001, I2 = 90%) and 48 h postoperatively (MD = -0.43; 95% CI: -0.52, -0.34; P < 0.00001, I2 = 96%). Moreover, DEX reduced analgesics consumption during the first 24 h (standardized mean difference [SMD] = -0.25; 95% CI: -0.34, -0.16; P < 0.00001, I2 = 91%) and the number of resuscitation analgesics administered (odds ratio [OR] = 0.54; 95% CI: 0.44, 0.66; P < 0.00001, I2 = 72%). Furthermore, DEX improved patient satisfaction (OR = 3.55; 95% CI: 2.36, 5.35; P < 0.00001, I2 = 60%), and reduced incidence of side effects, such as postoperative nausea and vomiting (PONV) (OR = 0.47; 95% CI: 0.39, 0.57; P < 0.00001, I2 = 59%) and pruritus after surgery (OR = 0.45; 95% CI: 0.30, 0.68; P = 0.0001, I2 = 0%). Besides, DEX attenuates inflammatory cytokine levels, such as IL-6 (MD = -5.73; 95% CI: -8.34, -3.12; P < 0.00001, I2 = 91%) and TNF-α（MD = -0.63; 95% CI: -0.76, -0.50; P < 0.00001, I2 = 89%). Finally, DEX increased the risk of bradycardia (OR = 1.66; 95% CI: 1.12, 2.45; P = 0.01, I2 = 15%), but the complication of hypotension did not differ between the two groups (OR =1.30; 95% CI: 0.84, 2.04; P = 0.25, I2 = 0%). Conclusions: DEX is used for postoperative PCIA analgesia, which can significantly improve the analgesic effect, effectively control postoperative inflammatory response, reduce the dosage and adverse reactions of analgesics, and improve postoperative patient satisfaction. Of course, the impact of the immunosuppressive effect of DEX on the prognosis of patients needs further study.